Assessing potentially time‐dependent treatment effect from clinical trials and observational studies for survival data, with applications to the Women's Health Initiative combined hormone therapy trial. (17th February 2015) - Yang, Song; Prentice, Ross L.
<x xml:space="preserve">Abstract</x> For risk and benefit assessment in clinical trials and observational studies with time‐to‐event data, the Cox model has usually been the model of choice. When the hazards are possibly non‐proportional, a piece‐wise Cox model over a partition of the time axis may be considered. Here, we propose to analyze clinical trials or observational studies with time‐to‐event data using a certain semiparametric model. The model allows for a time‐dependent treatment effect. It includes the important proportional hazards model as a sub‐model and can accommodate various patterns of time‐dependence of the hazard ratio. After estimation of the model parameters using a pseudo‐likelihood approach, simultaneous confidence intervals for the hazard ratio function are established using a Monte Carlo method to assess the time‐varying pattern of the treatment effect. To assess the overall treatment effect, estimated average hazard ratio and its confidence intervals are also obtained. The proposed methods are applied to data from the Women's Health Initiative. To compare the Women's Health Initiative clinical trial and observational study, we use the propensity score in building the regression model. Compared with the piece‐wise Cox model, the proposed model yields a better model fit and does not require partitioning of the time axis. Copyright © 2015 John Wiley & Sons, Ltd.